Pengembangan Media Pembelajaran Berbasis PBL Terintegrasi Karakter Percaya Diri untuk Meningkatkan Pemecahan Masalah Matematika SMA - Elva Kurnia Putri; Meria Ultra Gusteti; Khairul Azmi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Research is motivated by the low problem-solving ability of students in learning mathematics. The purpose of this study was to determine the validity, effectiveness and practicality of interactive learning media based on problem based learning integrated self-confidence to improve students' problem-solving skills. The subject of this research is class XI SMA Negeri 5 Padang. The method in this research is the development research method with the ADDIE development model. The data collection instrument used was a validation questionnaire given to the validator to determine the validity of the product, and a questionnaire response from educators and students to determine the practicality of the product, as well as test instruments in the form of pretest and posttest to determine the effectiveness of the product. The results of the analysis of the data obtained were declared very valid with an average score of 90,7%. The results of the practicality test of teacher responses stated that the interactive learning media developed was very practical to be used with an average score of 100%, while the practicality test of students was declared practical with an average score of 85%. The results of the effectiveness test were obtained from the N-Gain of 0.48 with the medium category. This proves that problem based learning-based interactive learning media that integrate self-confidence to improve students' problem-solving skills is worthy of being used as a learning resource.